Occurrence of physical therapy consultations in the last 12 months among adults from a medium sized Brazilian city - Zanuto, Éverton Alex Carvalho [UNESP]; Mantovani, Alessandra Madia [UNESP]; Codogno, Jamile Sanches [UNESP]; Christofaro, Diego G. Destro [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Torres, Wésley [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Cardoso, Jeffesron Rosa [UNESP]; Vanderlei, Luiz Carlos Marquez [UNESP] (My University, 2015)
Cross-sectional design. Introduction: Physical Therapy is a profession with a diversity of methods and fields, and although it extends to all age groups with a huge number of clinics, the occurrence of searches for physiotherapists is still low. Aim: To analyze the occurrence of physical therapy consultations in the past 12 months among adults in Presidente Prudente, as well as to identify some variables associated with the outcome. Methods: The population (n=743) had a mean age of 49.9±17.3 years. The procedures set out the dependent variable: physical therapy consultation and independent variables: low back pain and physical activity during leisure time and at work, respecting the confounding factors. Results: The occurrence of physiotherapy consultations in the last 12 months was 21%, which was more frequent among adults of 30-44.9 years (OR=2.02 [1.02-3.99]) and for those with low back pain (OR=2.18 [1.18-4.06]). Conclusion: Physical therapy utilization is an outcome with a low rate, which is associated with low back pain among adults at a productive age.